2019
DOI: 10.1002/adem.201900327
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic‐Deposition of Graphene and Microstructure and Friction Behavior of Ni–Graphene Composite Coatings

Abstract: Ni–graphene composite coatings with promising friction reduction and wear resistance are successfully deposited on magnesium alloys substrate by an integrative approach involved electrophoresis and pulse electrodeposition. The optimization parameters for electrophoretic deposition are explored extensively. The effect of duty cycle on microstructure, micro‐indentation hardness, friction, and tribological properties for Ni–graphene composite coatings are investigated. The Ni matrix exhibits most refined at 60% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The change of the average nickel 2 presents the reported microhardness of nickel-graphene nanocomposite coatings. Comparing to other reports, the obtained results are in line with the earlier report by Dong et al, 58 in which using graphene as an additive component for the nanocomposite. Some other studies reported very high hardness coatings.…”
Section: Characterization Of Ni/gnps Nanocomposite Coatingssupporting
confidence: 92%
“…The change of the average nickel 2 presents the reported microhardness of nickel-graphene nanocomposite coatings. Comparing to other reports, the obtained results are in line with the earlier report by Dong et al, 58 in which using graphene as an additive component for the nanocomposite. Some other studies reported very high hardness coatings.…”
Section: Characterization Of Ni/gnps Nanocomposite Coatingssupporting
confidence: 92%
“…In the calculation results shown in Figures 2-5, the materials forming substrates are specified and, in particular, the notation BLG or Gr indicates the absence of a substrate. also interesting to mention that composite coatings composed of graphene and nickel were experimentally shown to be performant in reducing friction [34][35][36].…”
Section: The Effect Of Substrates On the Nanofriction Of The Graphene...mentioning
confidence: 99%
“…As a kind of wear-resistant coating, Nickel-based composite coating features high hardness and good wear resistance and is widely used for improving the surface properties of substrate materials. Researchers prepared Ni-P [5], Ni-W [6], Ni-B [7], Ni-Mo [8], Ni-Zn [9], Ni-Cu [10], Ni-Fe [11], Ni-Graphene [12] and other nickel-based composite coatings on different substrates to improve the hardness of the substrates and strengthen their wear resistance. Because the nickel-base coating is made from environmentally friendly and economical materials, it has become a substitute for traditional coatings such as Cr.…”
Section: Introductionmentioning
confidence: 99%